Curation: A Global Collaborative Challenge - Bridget Robinson (International Journal of Digital Curation, 2008)
This article provides some background to the Digital Curation Centre and concentrates on a brief overview of the aims of the 3rd International Digital Curation Conference to be held in Washington, D.C. this December, together with information on the array of prominent speakers.